(untitled) (Trabalho & Educação, 2016)
The high school is a privileged field for the development of educational projects aimed at the qualification of young people for the labor market. However, the strong evasion and the lack of identity and meaning have caused an explicit failure of such projects. Earlier this decade, the National Curriculum Guidelines for High School brought the Work as an educational principle and a training proposal that would allow not only students but also educators to articulate the knowledge with its transforming action. At the same time in 2012, the development of a curriculum project that focuses on employability aimed at high school began in flagrant inconsistency with the CGHSs. This article aims at the critical analysis of the proposals on the basis of Work and Employability categories and authors as Marise Ramos, Pablo Gentili and Marx. __ Ensino Médio é um campo privilegiado para o desenvolvimento dos projetos educacionais voltados à qualificação dos jovens para o mercado de trabalho. No entanto, a forte evasão e a carência de identidade e significado têm provocado um explícito fracasso de tais projetos. No início desta década, as Diretrizes Curriculares Nacionais para Ensino Médio (DCNEM) trouxeram o trabalho como princípio educativo e uma proposta de formação que possibilitasse não só aos educandos, mas também aos educadores articular conhecimento e ação transformadora. Concomitantemente, em 2012, iniciou-se o desenvolvimento de um projeto curricular nas escolas da Rede Estadual de Minas Gerais que privilegiou a empregabilidade como objetivo do Ensino Médio, em flagrante incompatibilidade com as DCNEM. Este artigo tem como objetivo a análise crítica dessas propostas com base nas categorias trabalho e empregabilidade e em autores como Marise Ramos, Pablo Gentili e Marx.